The Canada Emergency Wage Subsidy program and business survival and growth during the COVID-19 pandemic in Canada - Danny Leung; Huju Liu (Economic and Social Reports)
The COVID-19 pandemic had a major impact on businesses in 2020. In response, the Government of Canada introduced measures to support both individuals and businesses through the pandemic. The largest program for businesses was the Canada Emergency Wage Subsidy (CEWS). This paper presents firm-level evidence on the relationship between the usage of the CEWS programs and the survival and growth of businesses controlling for the pre-pandemic characteristics of businesses and where possible, their use of two other important programs, the Canada Emergency Business Account and the Canada Emergency Commercial Rental Assistance programs.